CLINICAL SIGNIFICANCE OF THE TRADITIONAL JAPANESE MEDICINE, KEISHIKA-SHAKUYAKU-TO, IN ABDOMINAL SPASTIC PAIN - Saito, Noboru; Mitsuhasi, Maki (International Journal of Research -GRANTHAALAYAH, 2023)
Primary goal: To assess the usefulness of Kampo for the outpatient treatment of abdominal spastic pain. Research Design: Retrospective study Methodology: A total of 85 patients with symptoms of abdominal spasmodic pain and diarrhea of unknown cause, including the patients with contraindications for anticholinergic drugs, were included in the study. The patient was administered oral Keishika-Shakuyaku-to (TJ-60: 7.5 g/day) to treat spastic pain and diarrhea. The degree of improvement in pain was evaluated using a numerical rating scale at the start of treatment and 3 months later and used as an indicator of continuation. Main outcomes and Results: Therapeutic effects were seen in 77.6% (66/85) of the included patients with the level of pain decreasing by over 50% 3 months after the first treatment. Additionally, no side effects from oral administration or adverse events leading to drug discontinuation were observed. Conclusions: Kampo, Keishika-Shakuyaku-to was found to reduce abdominal pain and diarrhea of unknown cause and could be used safely without causing significant side effects even in patients with contraindications for anticholinergic drugs.